Gender and academic-level variations in perceived effects of artificial intelligence on English majors’ critical thinking - Mariam Mardia; Md. Mahadhi Hasan (Institute of Advanced Engineering and Science, 2026)
Integrating artificial intelligence (AI) tools in English studies raises significant concerns about whether it would diminish critical thinking and cognitive skills. The research aims to analyze how English majors in Bangladesh perceive the impact of AI tools on their critical thinking skills with regard to gender and academic levels. A mixed-method approach was employed through a purposive sampling technique. Constructivist learning and the technology acceptance model (TAM) theories were used in the study. The research design employed two instruments: a survey administered to 245 students from the Bachelor of Arts (BA) and Master of Arts (MA) programs, and six in-depth interviews. The study analyzed quantitative data using descriptive statistics and an independent-samples t-test and qualitative interview data using thematic analysis. Key quantitative findings suggested that students widely recognized the usefulness of these tools across multiple academic areas, such as structuring writing, generating ideas, and goal setting (mean=4.31), indicating positive responses across all items. The t-test findings did not show statistically significant differences in gender or academic level; however, small effect sizes slightly favored male and MA students across all items. Additionally, AI tools helped students cope with cognitive stress by helping them meet deadlines. However, the interviewed participants expressed concern about ethical issues, including the potential for AI to plagiarize. Therefore, this study argues for a balanced approach to AI in education, highlighting its advantages while acknowledging its potential drawbacks and mitigating the challenges before implementation.